The Effect of Applying EthnoVlog Media to Increase Student Social Media Literacy - Lestari, Indah Beti; Darmawan, Deni; Dewi, Laksmi; Rahmawati, Yulia (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aimed to analyze the influence and improvement of the application of EthnoVlog media on students' social media literacy. This study used a quantitative approach. The product studied in this study was EthnoVlog media in the context of learning science on food and beverage additives carried out at MTs Al Uswah Bergas and SMP Negeri 1 Bergas. Purposive sampling was the method of sampling employed in this study. The researcher used the pre-experimental design approach, type one group pretest-posttest (single group pretest-posttest). According to the findings of the paired sample t-test on the SPSS output, H0 was rejected, and Ha was approved since the significance value was 0.000 < 0.005. This proves that EthnoVlog media influences social media. In addition, the influence of EthnoVlog media also increased students' N-Gain scores by 0.33 for SMP students in the medium category and by 0.26 in the low sort for MTs students. This shows that EthnoVlog media increases students' social media literacy. Based on the results of the data analysis, it can be concluded that EthnoVlog media in the context of learning science is categorized as a learning media that can influence students' social media literacy.